2014
DOI: 10.1007/s12015-014-9559-3
|View full text |Cite
|
Sign up to set email alerts
|

Human Periosteal Derived Stem Cell Potential: The Impact of age

Abstract: There is a great deal of interest in the understanding of possible age-related changes in Mesenchymal Stem Cells in view of their use for regenerative medicine applications. Given to the outmost standing of periosteum in bone biology and to probe data for a cell-based therapy promoting graft osseointegration in the elderly, we tried to identify specific aging markers or pattern of expression in human periosteal precursor cells. Immunohistochemical detection of Ki67 and p53, Nitric Oxide production and qRT- PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Such equation may customize both periodontal and orthodontic consideration in adult patients, especially determining whether bone augmentation surgery was needed to aid orthodontic therapy, commonly recognized as surgically facilitated orthodontic therapy [SFOT] [32] or periodontally accelerated osteogenic orthodontics [PAOO]) [33] . Our present equation further supports the conception that bodily retraction would lead to proximity of root apex to palatal cortical plate and extensive alveolar bone resorption [34] ,and this jeopardy is particularly pertinent in adults as numbers and regeneration capability of osteoblasts in the periosteum reduces with aging [35] .…”
Section: 533×apex Displacement (T1-t0))supporting
confidence: 84%
“…Such equation may customize both periodontal and orthodontic consideration in adult patients, especially determining whether bone augmentation surgery was needed to aid orthodontic therapy, commonly recognized as surgically facilitated orthodontic therapy [SFOT] [32] or periodontally accelerated osteogenic orthodontics [PAOO]) [33] . Our present equation further supports the conception that bodily retraction would lead to proximity of root apex to palatal cortical plate and extensive alveolar bone resorption [34] ,and this jeopardy is particularly pertinent in adults as numbers and regeneration capability of osteoblasts in the periosteum reduces with aging [35] .…”
Section: 533×apex Displacement (T1-t0))supporting
confidence: 84%
“…Despite these advances, there are still few comparable data in the literature on long-term in vitro and in vivo characterization of bioprinted and biofabricated bone constructs. The improve accuracy of in silico predictive models would also reduce the numbers of animals used in in vivo studies (Fedorovich et al, 2011; Ferretti et al, 2015; Vozzi et al, 2016). …”
Section: Clinical Translationmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) no systematic medical compromising conditions; (2) no medications affecting periodontal status; (3) only light smokers were included (< 10 cigarettes/day); (4) not pregnant or lactating; (5) familial aggregation (history of periodontitis in parents or siblings); (6) presence of at least two teeth with probing pocket depth (PPD) ≥ 6 mm and CAL ≥ 5 mm associated with an intrabony defect of at least 3 mm as detected in diagnostic periapical radiographs; (7) full mouth plaque score (FMPS) ≤ 20%; (8) bleeding on probing score (BoP) ≤ 20%; (9) teeth had to be vital or properly treated; (10) no furcation involvement of the teeth presenting the intraosseous defects; (11) the width of keratinized tissue on the facial aspect of the selected teeth ≥ 2 mm.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The high osteogenic potential of jaw periosteal cells, especially MSCA-1 + fraction, is closely related to the expression of lipoprotein receptor-related protein 6 (LRP-6), stanniocalcin 1 (STC-1), and tissue inhibitor of metalloproteinases-4 (TIMP-4) [5]. Periosteal cell populations modify their potential with age, with a significant increase in IL-6 mRNA expression and receptor activator of nuclear factor kappa-B ligand/osteoprotegerin ratio [6]. In vivo studies indicated that PDPCs are indispensable for bone graft healing and remodeling [7].…”
Section: Introductionmentioning
confidence: 99%